The future of rock and roll 97X WOXY and the fight for true independence - James, Robin, 1978- (The University of North Carolina Press, 2023)
"In 1989, an Ohio radio station called WOXY launched a sonic disruption to both corporate rock and to its conservative home region, programming an omnivorous range of genres and artists while being staunchly committed to local independent art and media. In the 1990s, as alternative rock went mainstream and radio grew increasingly homogeneous, WOXY gained international renown as one of Rolling Stone's 'Last Great Independent Radio' stations. Robin James uses WOXY's story to argue against a corporate vision of independence-in which everyone fends for themselves-and in favor of an alternative way of thinking and relating to one another that disrupts norms but is nevertheless supported by communities"--